Adoption of information systems in organizations: Understanding the role of institutional pressures in a collectivist culture. Issue 2 (26th November 2019) - Arshad, Muhammad; Farooq, Mariam; Afzal, Sadia; Farooq, Omer
Abstract : Purpose: The purpose of this paper is to determine the factors influencing the adoption of new information systems (IS) in organizations. Based on the institutional theory, this research proposes that organizations may induce their employees to adopt new IS by creating three types of institutional pressure: coercive, normative and mimetic. It is further argued that the effects of these three institutional pressures on employees' new IS usage depend on their cultural orientations. Design/methodology/approach: Model testing relies on data collected from 370 banking sector employees during the implementation of a new "customer relationship management" system. The hypothesized model was tested by using the structural equation modeling technique in MPlus 7.0. Findings: The findings of this research reveal that institutional pressures (coercive, normative and mimetic) have positive effects on employees' attitudes to using the new IS, which, in turn, positively influences their IS usage. In addition, collectivism strengthens the positive effect of coercive and normative forces on attitudes to using the new IS. Conversely, collectivism weakens the effect of the mimetic force on employees' attitudes to using the new IS. Originality/value: This research is among pioneering studies that explain the effect of institutional pressures (coercive, normative and mimetic) on employees' IS usage. It is the first study of its nature that demonstrates that each of the three institutional pressures has differential effects on employees with highly collectivist orientations in comparison with employees with low collectivist orientations.